2011
DOI: 10.1103/physrevb.84.104507
|View full text |Cite
|
Sign up to set email alerts
|

Vortex imaging and vortex lattice transitions in superconducting Sr2RuO4single crystals

Abstract: Scanning Hall probe microscopy has been used to study vortex structures in very-high-quality single crystals of the unconventional superconductor Sr 2 RuO 4 (T c ∼ = 1.5 K). In none of our samples do we find credible evidence for the existence of the spontaneous fields or chiral domains predicted for the expected time-reversal symmetry-breaking order parameter. Even in our highest-quality samples we observe very strong vortex pinning and anomalous broadening of vortex profiles. The best samples also exhibit a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 34 publications
5
65
0
Order By: Relevance
“…Neutron scattering study revealed the existence of a square rather than the traditional triangular vortex lattice over a large range of temperatures and magnetic fields applied along the c axis [6]. Surprisingly, vortex lattices were observed [7] at a field much lower than the lower critical field H c1 c = 50 Oe [8]. More specifically, the triangular Abrikosov vortex lattice was observed at a field as low as 5.4 Oe and a wellordered square lattice was found to form for fields above 12.7 Oe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron scattering study revealed the existence of a square rather than the traditional triangular vortex lattice over a large range of temperatures and magnetic fields applied along the c axis [6]. Surprisingly, vortex lattices were observed [7] at a field much lower than the lower critical field H c1 c = 50 Oe [8]. More specifically, the triangular Abrikosov vortex lattice was observed at a field as low as 5.4 Oe and a wellordered square lattice was found to form for fields above 12.7 Oe.…”
mentioning
confidence: 99%
“…In an applied magnetic field, previous studies of the few-vortex states of mesoscopic Type II superconductors suggest that the free energy of the sample will be minimized if the ring is decorated by vortices [21]. In small fields, these vortices will be driven in and out of the ring because of the weak pinning potentials in crystalline Sr 2 RuO 4 and the lack of sample space to form a square vortex lattice expected for this field regime [7]. For the two thick-wall rings, on which two different periods of resistance oscillations were found, we note that the wall thickness, (w ∼ 4.8ξ(0)) and (w ∼ 5.5ξ(0)), respectively, would allow two vortices along the radial direction of the ring (the nominal size of the normal core of a vortex is 2ξ(0)).…”
mentioning
confidence: 99%
“…According to contemporary concepts (see, for example, [5][6][7]), such a behavior of the ρ ab (Т) dependences can be caused by the transition to the so-called pseudogap state, characteristic for the "underdoped" compositions of HTSC compounds. A certain role in this is played by the presence of structural and kinematic anisotropy in the system [38][39][40][41][42]. On the other hand, it cannot be completely excluded that this feature can also be partially caused due to the presence of an additive contribution to the conductivity from impurity phases with higher T c .…”
Section: Resultsmentioning
confidence: 96%
“…3 and, for example, [11]). A certain role in this is played by the presence of structural and kinematic anisotropy in the system [12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%